An Updated Comprehensive Review on Novel Drug Delivery Systems (NDDS) In the Pharmaceuticals - Rao Khadam, Vinay Kumar; Singh, Ravindra Pal; Prajapati, Deepak; Yunus, Mohammad; Prajapat, Balkishan; Kumar Rai, Santosh; Kumari, Prakriti; Gogoi, Dipon (Asian Journal of Pharmaceutical Research and Development, 2024)
The field of pharmaceutical sciences has witnessed a paradigm shift with the advent of Novel Drug Delivery Systems (NDDS), which aim to enhance therapeutic efficacy, reduce side effects, and improve patient compliance. This comprehensive review explores the latest advancements and innovations in NDDS, encompassing a diverse range of delivery platforms and strategies.(NDDs are transforming the landscape of pharmaceutical treatment, offering unparalleled potential for enhanced therapeutic efficacy, improved bioavailability, controlled release, targeted delivery, and enhanced stability. This comprehensive review explores the diverse landscape of NDDS, highlighting recent advancements and addressing key challenges. Prominent NDDS include liposomes, nanoparticles, micelles, polymeric drug conjugates, monoclonal antibodies, implants, and patches. Each system possesses unique properties and applications, tailored to specific drugs and therapeutic needs. Recent breakthroughs in targeted nanocarriers, gene therapy vectors, and 3D-printed personalized dosage forms are pushing the boundaries of innovation. The main highlights of the present review firstly the basics on NDDs, the several approaches of nano drug carriers for the drug delivery with their preparation methods and example. The middle version of review discuss the recent advancements techniques in the preparation of NDDs carriers and lastly the marketed formulation of particular drug carrier.